FRONTIERS OF EXCLUSION IN EDUCATIONAL OPPORTUNITIES AND INCLUSIVE EDUCATION SYSTEM (Proceedings of the World Disability & Rehabilitation Conference, 2018)
Schools are main public spaces for social development and they provide formative education to students as a secondary social institution throughout the world. Social exclusion and unequal educational opportunities are growing phenomenon in both developed and under developed countries.  Inclusive education ensures equal education opportunities for visually, physically and financially handicapped children regardless of their inabilities, class or caste. The national education policy of Sri Lanka comprises a special section on implementing inclusive education policy within the country but many disabled students have been excluded and isolated within the present education system. An inclusive school caters for a non discriminative environment for disabled or special needs children where it leads to main goals of education like social cohesion and social justice. The focal aim of inclusive education system is to ensure the right of the disabled and special needs students to study in mainstream schools where the right to education has been promoted through not marginalizing the disabled students. The current education system should transformed to cater diversity of students’ learning needs despite of social, cultural and physical differences and enhancing learning motivation, adaptability and abilities. The study aims at the exclusion of educational opportunities of disable students and the primary data was collected through case studies and the additional data was collected through diverse secondary sources. The findings of the study ensures implementation of inclusive education policy which has to be reconstructed using homogenous approaches, which develop an education model considering diversity of needs, abilities and identities where teaching-learning process comprises flexibility and adaptability to cater diverse needs of student population.
Keywords: Social exclusion; Inclusive education; Social cohesion; Social justice; Homogenous approaches